(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe treatment adherence among hypertensive outpatients at Me Linh General Hospital and analyze several related factors in 2025. Subjects and Methods: A cross-sectional descriptive study was conducted on 361 hypertensive outpatients at Me Linh General Hospital in 2025. Data were collected using a structured questionnaire, including general characteristics, knowledge of hypertension and its treatment regimen, and the 8-item Morisky Medication Adherence Scale. Descriptive statistics and odds ratios with 95% confidence intervals were used to identify factors associated with non-adherence. Results: The rate of adherence to antihypertensive medication was 83.9%, while 16.1% of patients were non-adherent. The proportion of patients with adequate knowledge of hypertension and its treatment regimen was 45.7%. Factors significantly associated with non-adherence included low educational level (OR=2.98; 95%CI: 1.62–5.48), absence of complications (OR=7.86; 95%CI: 3.63–17.02), inadequate knowledge (OR=2.54; 95%CI: 1.36–4.74), living alone (OR=6.00; 95%CI: 2.30–15.64), and lack of family reminders (OR=3.50; 95%CI: 1.57–7.79). Age group was not significantly associated with adherence (p>0.05). Conclusion: Treatment adherence among hypertensive outpatients was relatively high; however, patients’ knowledge of hypertension and its treatment remained limited. Health education and stronger family support should be enhanced to improve treatment adherence.